Biomarkers and Microscopic Colitis: An Unmet Need in Clinical Practice - Pisani, Laura Francesca; Tontini, Gian Eugenio; Marinoni, Beatrice; Villanacci, Vincenzo; Bruni, Barbara; Vecchi, Maurizio; Pastorelli, Luca (Frontiers in Medicine, 2017)
One of the most common causes of chronic diarrhea is ascribed to Microscopic colitis (MC). MC is classified in subtypes: collagenous colitis (CC) and lymphocytic colitis (LC). Patients with MC report watery, non-bloody diarrhea of chronic course, abdominal pain, weight loss and fatigue that may impair patient’s health-related quality of life. A greater awareness, and concomitantly an increasing number of diagnoses over the last years, has demonstrated that the incidence and prevalence of microscopic colitis are on the rise. To date, colonoscopy with histological analysis on multiple biopsies collected along the colon represents the unique accepted procedure used to assess the diagnosis of active MC and to evaluate the response to medical therapy. Therefore, the emerging need for less-invasive procedures that are also rapid, convenient, standardized and reproducible, has encouraged scientists to turn their attention to the identification of inflammatory markers and other molecules in blood or feces and within the colonic tissue that can confirm a MC diagnosis. This review gives an update on the biomarkers that are potentially available for the identification of inflammatory activity, related to CC and LC.